2003
DOI: 10.1103/physrevc.68.065203
|View full text |Cite
|
Sign up to set email alerts
|

Λ(1405)production in theπpK0πΣreaction

Abstract: We discuss the mechanisms that lead to Λ(1405) production in the π − p → K 0 πΣ reaction. The problem has gained renewed interest after different works converge to the conclusion that there are two resonances around the region of 1400 MeV, rather than one, and that they couple differently to the πΣ andKN channels. We look at the dynamics of that reaction and find two mechanisms which eventually filter each one of the resonances, leading to very different shapes of the πΣ invariant mass distributions. The combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
152
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 28 publications
8
152
0
Order By: Relevance
“…Different experiments which favor mechanisms that give a bigger weight to one of these channels would lead to very different widths of the resonance. This is the case with the recent findings that the Λ(1405) resonance corresponds to actually two poles and different experiments favor one or the other pole, leading to different visible widths of the resonance [17,18,29].…”
Section: S = 1 I = 1/2mentioning
confidence: 71%
“…Different experiments which favor mechanisms that give a bigger weight to one of these channels would lead to very different widths of the resonance. This is the case with the recent findings that the Λ(1405) resonance corresponds to actually two poles and different experiments favor one or the other pole, leading to different visible widths of the resonance [17,18,29].…”
Section: S = 1 I = 1/2mentioning
confidence: 71%
“…This finding unveils the structure of the Λ(1405) as a superposition of two states [6,8], which have been studied both theoretically and experimentally [9]. The structure of the Λ(1405) has a large impact for the study of thē KN interaction [10], which is eventually important for the study of the kaonic nuclei and kaon condensation in the neutron star [11].…”
mentioning
confidence: 99%
“…The study of the present reaction, complemental to the one of Ref. [12] for the π − p → K 0 πΣ reaction, has shown that the quite different shapes of the Λ(1405) resonance seen in these experiments can be interpreted in favour of the existence of two poles with the corresponding states having the characteristics predicted by the chiral theoretical calculations. Besides demonstrating once more the great predictive power of the chiral unitary theories, this combined study of the two reactions gives the first clear evidence of the two-pole nature of the Λ(1405).…”
mentioning
confidence: 77%